Visual Perspectives in Episodic Memory and the Sense of Self - Lin, Ying-Tung (Frontiers in Psychology, 2018)
The connection between memory and self-consciousness has been a central topic in philosophy of memory. When remembering an event we experienced in the past, not only do we experience being the subject of the conscious episode, but we also experience being the protagonist in the memory scene. This is the “phenomenal presence of self.” To explore this special sense of self in memory, this paper focuses on the issue of how one identifies oneself in episodic simulation at the retrieval of memory and draws attention to the field and observer perspectives in episodic memory. Metzinger (2013a; 2017; 2013b) recently introduced the concept of the phenomenal unit of identification (UI) to characterize the phenomenal property that gives rise to the conscious experience of “I am this.” This paper shows how observer-perspective remembering provides an interesting opportunity for studying the sense of self. It is argued that observer-perspective remembering is a stable state of consciousness that is distinct from autoscopic phenomena with respect to the dimensions of minimal phenomenal self (MPS). Together, the notion of UI and the particular style of remembering offer a way of understanding the phenomenal presence of self, and three possible ways in which phenomenal properties constitute UI in memory are raised. The study of perspectives in episodic simulation may prompt new empirical and conceptual issues concerning both the sense of identity and the relationship between minimal phenomenal self and extended self.